TRAINING AND ASSISTANCE IN APPLICATION OF BASIC EDUCATION DATA FOR OPERATORS OF SMP NEGERI 3 MUARA TIGA - Herinto Sidik Iriansyah; Iswadi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Muara Tiga State Junior High School (SMP) is one of the public junior high schools located in Muara Tiga District. All administrative and student learning activities are carried out manually. This hampers administrative services and services to parents of students. For the 2020/2021 school year, SMP Negeri 3 Muara Tiga has started using the Dapodik application or Basic Education Data. An open source-based education data collection and management system by implementing a centralized and web-based database system that can be accessed online and in real time. Based on observations made at SMP Negeri 3 Muara Tiga, the school operator at SMP Negeri 3 Muara Tiga consists of 1 person who is also in charge of entering school data, student data and teacher / employee data into the central database server both offline and online. and can be directly accessed by the District Education Office. The method of implementing community service activities is carried out using training methods and operator assistance for the Dapodik application. Activities start from the installation process, registration, dashboard management to training and assistance in filling out school data, student data and teacher / employee data. Operator training and assistance in using the Dapodik application is carried out for 1 month, namely in May 2021 as many as 1 operator accompanied by the school principal. Evaluation of training and mentoring activities is carried out continuously until the operator understands how the dapodik application business process is and is able to fill in data quickly, completely, validly, accountable and up to date.